Five brilliant scientists / by Lynda Jones ; illustrations by Ron Garnett. - Jones, Lynda (New York : Scholastic, 2000)
Describes the early lives and notable achievements of five black scientists, Susan McKinney Steward, George Washington Carver, Ernest Everett Just, Percy Lavon Julian, and Shirley Ann Jackson.
Keywords: African American scientists -- Biography -- Juvenile literature